2013
DOI: 10.1186/1472-6882-13-184
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese propolis disturbs glycolytic metabolism of human colorectal cancer in vitro

Abstract: BackgroundPropolis is a resin collected by bees from plant buds and exudates, which is further processed through the activity of bee enzymes. Propolis has been shown to possess many biological and pharmacological properties, such as antimicrobial, antioxidant, immunostimulant and antitumor activities. Due to this bioactivity profile, this resin can become an alternative, economic and safe source of natural bioactive compounds.Antitumor action has been reported in vitro and in vivo for propolis extracts or its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Upregulation of the MCT1 and MCT4 isoforms has been described in various malignancies, being previously been explored as targets in cancer therapy . Although only a small number of studies have investigated the role of MCT expression in brain tumors, the studies universally support the importance of MCTs, particularly MCT1 in these tumors . Our group reported that MCT1 is the most prevalent MCT isoform expressed in the plasma membrane of GBM cells and that its expression is upregulated in regions of hypoxia .…”
Section: Introductionmentioning
confidence: 78%
“…Upregulation of the MCT1 and MCT4 isoforms has been described in various malignancies, being previously been explored as targets in cancer therapy . Although only a small number of studies have investigated the role of MCT expression in brain tumors, the studies universally support the importance of MCTs, particularly MCT1 in these tumors . Our group reported that MCT1 is the most prevalent MCT isoform expressed in the plasma membrane of GBM cells and that its expression is upregulated in regions of hypoxia .…”
Section: Introductionmentioning
confidence: 78%
“…The majority of patients will succumb to the disease. Consequently, the medical application of propolis in cancer therapy could improve the effectiveness of chemotherapy (Frozza et al, 2013;Lin et al, 2013;Valença et al, 2013). Studies of various tumour cell lines have pointed to BRP and its derivatives as potential components of cancer treatment Frozza et al, 2013;Kamiya et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Propolis and its isolated constituents are suggested to serve as in vitro and in vivo antitumoural and immunomodulatory agents (Frozza et al, 2013;Orsolić , Saranović , & Basić , 2006;Orsolić , Terzić , Mihaljević , Sver, & Basić , 2005;Valença et al, 2013). In fact, propolis has cancer-preventive and antitumour properties through mechanisms that include cell-cycle arrest, induction of apoptosis, and inhibition of cancer cell proliferation and tumour growth Cuesta-Rubio, Frontana-Uribe, Ramirez-Apan, & Cardenas, 2002;Frozza et al, 2013;Kamiya, Nishihara, Hara, & Adachi, 2012;Valença et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, in vitro cell culture studies on the cytotoxic effects of propolis extracts from different regions have shown noteworthy findings (15)(16)(17)(18)(19)(20)(21)(22). In this context, the anticarcinogenic effects of propolis originated from diverse geographies were studied on breast cancer cell lines (BCCLs) (23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%